Outsourcing Strategy With Patent Licensing in an Electronic Product Supply Chain - Jiaguo Liu; Rui Sun; Fan Liu (IEEE Access, 2020)
An electronic product like a smartphone might involve hundreds of thousands of patents. The risks caused by infringement make it necessary for enterprises to consider patent licensing when outsourcing production activities in the electronics industry. This paper studies the outsourcing strategy considering patent licensing in an electronic product supply chain composed of a patent-holding firm, an original equipment manufacturer (OEM) and a contract manufacturer (CM). In addition to outsourcing manufacturing to the CM, OEM also considers outsourcing the patent license obtaining as well. We construct two outsourcing modes, called Turnkey and Consignment. No matter under which outsourcing mode, the patent-holding firm will charge unit royalty and a fixed fee paid in a lump sum. The results show that the OEM tends to choose Consignment without considering fixed fees, while the CM prefers Turnkey. When considering fixed fees, the patent-holding firm could align their preferences by coordinating fixed fees borne by OEM and CM. What’s more, considering the environmental pollution caused by the production of electronic products, both strategies may lead to higher social welfare than the other strategy.